(untitled) (Revista Científica Compendium, 2019)
The essay makes a brief philosophical reflection that disputes about the truth and its meaning in the current sciences. It is based on the theoretical contributions of Georges Balandier in his work “El desorden” (1988), to debate the understanding of the cosmos that evolves from Mechanism to Entropy; the behavior of complex and open systems and the necessity to adapt the way of knowing them. Cities are metaphorically outlined as “thermodynamic” systems. It is concluded that epistemologically, the foundation of the research of the public management of the cities, starts from assuming its object as a complex and open system, suggesting that the search for consensual truth and the application of socio-constructionist postulates seem to be the more pertinent way of knowing, in this case.